Big Data Analytical Tools, Challenges and Applications: A Survey - Saraswathi, M (International Journal of Computer Sciences and Engineering, 2025)
In this paper presents the term what exactly means “Big data”. we first investigate how big data is, and what are the recent technologies developed for big data. Due to this, we identify the big data applications including enterprise management, Internet of Things, online social networks, media and entrainment and healthcare. The various Challenges faced in large data management include scalability, unstructured data, accessibility, real time analytics, fault tolerance and many more. This survey is concluded with problems to be identified and future directions.